A boa-fé objetiva na concessão dos incentivos fiscais - Lima, Humberto Antonio Barbosa (2011)
This essay analyzes tax incentives concepts and existing discussions on national and foreing doctrine, especially in countries that influence our legal culture, such as Germany, United States of America, Spain, Italy and England, providing a detailed study about the requirements that must be observed to ensure that there be a legitimate concession of the same. All this using as argument the Constitutional Charter and the development of the Law, mainly through the principle of objective good faith, which acts as the limiting principle of administrative discretion in granting such tax incentives, as well as creative element of the new duties for the public managers in order to be more effective, efficient and transparent compliance with the pact between the government and society and the objectives pursued by the last. Always chasing a strong argument through a broad historical and philosophical analysis of the institutes discussed. Thus, through studies that reveal the necessary incidence of objective good faith in granting tax incentives to achieve the constitutional purposes, this work does not merely disclose what is wrong, but provides solutions to modify reality hitherto existing, ie, introduces ways to reduce the encumbrance of the odious and ineffective tax incentives in society and to redirect these values unjustly destinated for obscure interests to achieve the real reasons for the existence of tax incentives, especially economic development through the reduction of regional and social inaqualities and poverty eradication